ANALISIS KESALAHAN BERBAHASA INDONESIA DALAM PENULISAN CERITA PENDEK SISWA KELAS VIII SMP NEGERI 3 ABIANSEMAL TAHUN AJARAN 2023/2024 - Maryani, Ni Putu Saptari; Sukanadi, Ni Luh; Putra, I Komang Widana (JIPBSI (Jurnal Ilmiah Pendidikan Bahasa dan Sastra Indonesia), 2024)
Students are more familiar with the informal language used on social media than the formal language that should be used in writing short stories. This research use a desciptive qualitative approach. Based on the data obtained, in analyzing the data, language errors were found in students' short story writing, including 7 sentences found in the category of sentence ineffectiveness, 11 words found in diction, 4 words found in affixation, 33 sentences found in spelling, and the absorption elements found were 7 words. Based on the data obtained through this category, it was found that students still often use the wrong vocabulary when writing sentences and arranging words into sentences. The emergence of errors is caused by several causal factors that influence writing which researchers discovered from interviews with students. Mistakes made by class VIII students at SMP Negeri 3 Abiansemal when writing short stories include limited vocabulary mastery, habitual factors in using informal language, and the prestige of wanting to show the language of speakers and educated groups using words and sentences.